The melodrama of mobility : women, talk, and class in contemporary South Korea - Abelmann, Nancy (Book collections on Project MUSE., 2003)
How do people make sense of their world in the face of the breakneck speed of contemporary social change? Through the lives and narratives of eight women, The Melodrama of Mobility chronicles South Korea's experience of just such dizzyingly rapid development. Abelmann captures the mood, feeling, and language of a generation and an era while providing a rare window on the personal and social struggles of South Korean modernity. Drawing also from television soap operas and films, she argues that a melodramatic sensibility speaks to South Korea's transformation because it preserves the tension and ambivalence of daily life in unsettled times. The melodramatic mode helps people to wonder: Can individuals be blamed for their social fates? How should we live? Who can say who is good or bad? By combining the ethnographic tools of anthropology, an engagement with prevailing sociological questions, and a literary approach to personal narratives, The Melodrama of Mobility offers a rich portrait of the experience of compressed modernity in the non-West.